PROGRAM “METALLURGY” IS IMPORTANT ELEMENT OF SCIENTIFIC SUPPORT OF PROGRAM OF TECHNICAL RETOOLING OF ENERGY-INTENSIVE PRODUCTIONS OF THE REPUBLIC OF BELARUS - P. A. Vitjazj; A. A. Shipko; A. V. Tolstoj (Литьë и металлургия)
The main directions and developments of Program “Metallurgy” for years 2007–2010 are given.